ANALYSIS OF FIGURATIVE LANGUAGE IN THE LYRICS OF THE SONG ENTITLED 'I SEE THE LIGHT' IN THE DISNEY MOVIE TANGLED - Ni Putu Anggie Kusuma Wardhani (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2023)
This research aims to analyze the use of figurative language in the song entitled "I See the Light"from the Disney movie "Tangled", focusing on semantic studies. In this context, the analysis offigurative language is conducted using the theoretical of Perrine's Theory (1969), which emphasizesunderstanding the formal elements in literature, including the expression of figurative language. Thisresearch method involves a descriptive qualitative analysis of the lyrics of the song "I See the Light",focusing on identifying and understanding the different types of figurative language used. In thecontext of Perrine's theory, the research explores how figurative language contributes to the overallmeaning and aesthetics of the song lyrics. The results of this study reveal five figurative languagescontained in the lyrics of the song "I See the Light" including; metaphor, simile, personification,imagery, and metonymy. The implications of this research can also help broaden the understandingof the application of Perrine's Theory in literary analysis involving audio-visual literary contexts suchas songs in animated films.